Ethics and Principles of Mu'amalah in Daily Life Based on Sharia - Akbar Rasyid, Maulana (ICO EDUSHA, 2024)
This article discusses how the ethics and principles of mu'amalah (social and economic relations in Islam) can be applied in everyday life. Mu'amalah teaches about justice, honesty, and benefits for everyone. This article tries to explain the rules of mu'amalah and practical ways to apply them. This research was conducted by reading and analyzing books and articles about mu'amalah. The results showed that the ethics of mu'amalah are very important for creating a just society Keywords: Transactions, sharia principles, ethics